Prognostic Factors and Efficacy of First‐Line Chemotherapy in Patients with Advanced Thymic Carcinoma: A Retrospective Analysis of 286 Patients from NEJ023 Study. (23rd March 2018) - Ko, Ryo; Shukuya, Takehito; Okuma, Yusuke; Tateishi, Kazunari; Imai, Hisao; Iwasawa, Shunichiro; Miyauchi, Eisaku; Fujiwara, Akiko; Sugiyama, Tomohide; Azuma, Keisuke; Muraki, Keiko; Yamasaki, Masahiro; et al.
Abstract: Background: The prognostic factors and the efficacy of first‐line chemotherapy remain unclear in patients with advanced thymic carcinoma. Materials and Methods: We conducted a multi‐institutional retrospective study named NEJ023 for patients with advanced thymic carcinoma. All patients without any indication of curative treatment were treated with chemotherapy from 1995 to 2014 at 40 institutions of the North East Japan Study Group. Results: A total of 286 patients with advanced thymic carcinoma were analyzed. First‐line chemotherapy included platinum‐based doublets in 62.2% of the patients, monotherapy in 3.5%, and other multidrug chemotherapy (e.g., cisplatin, doxorubicin, vincristine, and cyclophosphamide [ADOC]) in 34.3%. The median follow‐up period was 55.5 months, and the median overall survival (OS) from the start of first‐line chemotherapy was 30.7 months (95% confidence interval, 25.9–35.9 months). There was no significant difference in OS among different first‐line chemotherapy regimens (e.g., between carboplatin/paclitaxel and ADOC, median OS: 27.8 vs. 29.9 months). Masaoka‐Koga stage IVa and volume reduction surgery were favorable prognostic factors for OS in the multivariate analysis using the Cox proportional hazards model. Conclusion: The efficacy of each first‐line chemotherapy regimen for advanced thymic carcinoma did not vary significantly. Our results might support the adequacy of the use of carboplatin/paclitaxel as first‐line chemotherapy for these patients. Implications for Practice: Because of its rarity, there is limited information about prognostic factors and efficacy of chemotherapy in patients with advanced thymic carcinoma. This is the largest data set for those patients treated with chemotherapy. This study suggests there is no significant difference in efficacy between carboplatin/paclitaxel and cisplatin/doxorubicin/vincristine/cyclophosphamide for advanced thymic carcinoma. This result can support the adequacy of the selection of platinum doublets as treatment for those patients, rather than anthracycline‐based multidrug regimen. Abstract : This article evaluates the efficacy of chemotherapy in advanced thymic carcinoma, comparing chemotherapy regimens and identifying the patients most likely to benefit from chemotherapeutic regimens.